Absorbsi Antosianin Buah Anggur (Vitis vinifera) Pada Kertas Saring Whatmann No. 41 Dan Whatmann No. 42 Untuk Identifikasi Boraks - Deny Kurniawan; Vita Pramaningsih; Rusdi Rusdi; Oktavianti Dwi Lesmana (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Borax detection can be done using the flame test method, volumetric titration, spectrophotometric analysis, and qualitatively using natural materials such as curcumin and anthocyanins. The high content of anthocyanins in grapes has the potential to be utilized in acid-base titrations as an indicator of natural acid-base. The research objective was to determine the potential of anthocyanins in the flesh and skin of grapes in detecting natural borax which is absorbed on filter paper, Whatmann paper no. 41 and Whatmann paper no. 42. Then it was tested on samples of meatballs from 5 sellers in Samarinda Seberang to Mangkupalas village. The research method used is a quantitative analysis of the color changes that occur. Based on the research results, filter paper can have a better absorption that is shown with a dark color on Whatmann No. 41 and Whatmann No.42. Grape skin extract can detect borax more clearly than flesh by forming a dark purple ring when reacting with borax. In testing using meatball samples, the overall results showed that the samples contained borax. It was concluded that the filter paper from the absorption of grape skin anthocyanins could be used as an alternative in quantitatively testing the borax content in food.